Influence of ambient storage condition on the nutritional quality of selected freeze dried instant Nigerian soups - Raji, Akeem Olayemi (Array, 2020)
Traditional soups are culturally acceptable soups that are rich in nutrients, but conventional preservation methods such as reheating after use and frozen storage diminish their nutrient qualities. Freeze drying is a dehydration method which has a great ability to retain food nutrients, but there is scanty of scientific data on its application to Nigerian soups preservation. Soups (Ila, Ewedu, Ogbono and Kuka) were prepared using standard recipes, freeze-dried, packaged in polyvinylchloride and stored at ambient condition for 8 weeks. Moisture, protein, fat, crude fibre, ash, carbohydrate, iron, calcium, sodium, potassium, phosphorus and vitamins were determined at 14 days interval using standard methods. Data were analysed using ANOVA at p = 0.05. Moisture, protein, fat, crude fibre, ash and carbohydrate contents of the soups ranged from 6.33-7.57%, 25.93-43.86 %, 7.19-43.86 %, 13.52-17.16 %, 8.45-10.80 % and 0.65-27.97 % respectively. Iron, calcium, sodium, potassium and phosphorus varied from 9.26-13.47 mg/100g, 73.57-245.23 mg/100g, 150.78-281.72 mg/100g, 209.22-352.07 mg/100g and 286.18-363.52 mg/100g respectively. The predominant vitamins (mg/100g) were A (66.69-137.49), B (22.73-88.74) and E (64.20-207.23). Freeze-drying reduced soups moisture contents by 90.0-90.8 %, thus increased the concentrations of other constituents. The nutrients quality of the freeze dried soups was well maintained for a storage period of two months, but cannot be further guaranteed due to slight decrease in their fat contents which indicates an increase in lipid oxidation.